VD_FINDINFO HC / 2018 / 611 vom 25. Juni 2018 - VD Tribunal cantonal (2018)
GARDE ALTERNÉE, RELATIONS PERSONNELLES, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT | 176 al. 1 ch. 1 CC, 273 al. 1 CC, 276 al. 1 CC, 276 al. 2 CC, 285 CC